The Language of Persuasion in Grammarly's Advertisements on YouTube - Anisa; Neil Amstrong (ELITE: Journal of English Language and Literature, 2024)
This research analyzed the persuasion strategies in Grammarly’s advertisements on YouTube. The types of persuasion strategies derived from McPheat's linguistic tools to persuade (2010). This research focused on the linguistic tools to persuade, which include reframing, using someone’s name, mind reading, lost performative, cause and effect relationships, presupposition, universal beliefs, tag questions, and embedded commands.Therefore, this research aims to describe the types of persuasion strategies in Grammarly’s advertisements on YouTube based on McPheat linguistic tools to persuade (2010) theory. This research used a descriptive qualitative method. The source of data was taken from Grammarly’s advertisements published on YouTube inFebruary 2019-Oktober 2022. The researcher collected data by downloading, transcribing, watching videos and reading the script, capturing, conducting data reduction, coding, and then analyzing by presenting, describing, and interpreting the data using McPheat then concludes the data. The results showed that only 7 out of 17 types of persuasion strategies were found in a total of 20 data. Those are presupposition, cause and effect relationships, embedded commands, lost performative, universal beliefs, and reframing: change the time frame, and reframing: appeal to the positive intention behind the belief. The most dominant strategy is presupposition, which features other strategies in one data set. The conclusion is that effective communication relies on a successful exchange of information, and Grammarly achieves this through a diverse range of persuasivestrategies, ensuring its message is well-received by the targeted audiences.